2011
DOI: 10.1021/jm101514m
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of ortho-Carbaboranyl-Nε-Modified l-Lysine into Neuropeptide Y Receptor Y1- and Y2-Selective Analogues

Abstract: Nontoxic ortho-carbaborane is one of the most promising structure for boron neutron capture therapy (BNCT). For directed uptake of ortho-carbaborane by tumor cells, receptor-subtype selective neuropeptide Y (NPY) and its derivatives were modified with ortho-carbaborane. The derivative [F(7), P(34)]-NPY has been shown to be a breast cancer selective ligand that binds to the Y(1)-receptor subtype, whereas [Ahx(5-24)]-NPY selectively addresses Y(2)-receptor subtypes that are found in neuroblastoma cells. ortho-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 60 publications
2
56
0
1
Order By: Relevance
“…The statistical analysis of three to four independent experiments revealed an averaged EC 50 value of 1.73 nM for NPY and 2.30 nM for FP-NPY determined by impedimetric monitoring in comparison to 4.14 nM for NPY determined by IP accumulation assay. These values are in line with previously reported EC 50 values in a COS-7 IP-accumulation assay (Ahrens et al, 2011). This underlines the sensitivity and comparability of our impedance spectroscopy based NPY-activation monitoring to the established radio ligand based IP-accumulation assay.…”
Section: Characterization and Quantification Of Subtype Specific Npyrsupporting
confidence: 91%
See 1 more Smart Citation
“…The statistical analysis of three to four independent experiments revealed an averaged EC 50 value of 1.73 nM for NPY and 2.30 nM for FP-NPY determined by impedimetric monitoring in comparison to 4.14 nM for NPY determined by IP accumulation assay. These values are in line with previously reported EC 50 values in a COS-7 IP-accumulation assay (Ahrens et al, 2011). This underlines the sensitivity and comparability of our impedance spectroscopy based NPY-activation monitoring to the established radio ligand based IP-accumulation assay.…”
Section: Characterization and Quantification Of Subtype Specific Npyrsupporting
confidence: 91%
“…The peptide ligand pNPY (abbreviated as NPY), the Y1-receptor preferring [F7,P34]-NPY (abbreviated as FP-NPY) (Soll et al, 2001), the Y2-receptor preferring [Ahx5-24]-NPY (abbreviated as Ahx-NPY) (Rist et al, 1996) and the Y5-receptor preferring [Ala31, Aib32]-NPY (abbreviated as AAib-NPY) (Cabrele et al, 2000) were synthesized by solid phase peptide synthesis as described previously (Ahrens et al, 2011). For selective Y1R inhibition BIBP3226 (SantaCruz Biotechnology, USA) was used (Rudolf et al, 1994).…”
Section: Npy and Specific Receptor Agonists And Antagonistsmentioning
confidence: 99%
“…With respect to the great potential of NPY ligands as pharmaceuticals for various indications such as cancer [133134] and obesity [99], automated SPPS also offers a versatile repertoire. As an example, a method to produce radiolabeled Y 1 -receptor preferring agonists of NPY has been described, which could selectively target breast cancer cells and allowed specific tumor diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…In quantitative studies, the content of boron in the cancerc ells was found to exceed the significant amount of 10 9 boron atoms per cell. [10] Besides NPY,s everal other peptides have been proposed ast umor-targeting carriers:e xamples include somatostatin, epidermal growth factor,n eurotensin, substance P, gastrin-releasing peptide, insulin-like growth factor, [11] amelanocyte-stimulating hormone, cholecystokinin, vasoactive intestinal peptide, and bombesin. [12] In view of this large number of peptides,i ta ppears surprising that the cobalt bis(dicarbollide) anion 1 has never been incorporated into any tumor-selective peptided espite obvious possible advantages.…”
Section: Introductionmentioning
confidence: 99%
“…[14] To avoid theses ide effects, we designed an ew chargecompensated (zwitterionic) key intermediate of 1,w hich allows furtherm odifications with moieties of biochemical relevance, such as monosaccharides. The resulting buildingb locks were successfully coupled to the tumor-selective peptide [ F 7 ,P 34 ]-NPY [10] with retention of excellent Y 1 receptor activity.…”
Section: Introductionmentioning
confidence: 99%